Small ’t’ treaty Relationships Without Borders: Bear River First Nation, Clam Harvesters, the Bay of Fundy Marine Resource Centre and the World Forum of Fisher Peoples - Pictou, Sherry M. (Anthropologica, 2015)
Tully, Asch and Borrows assert that while treaties are subject to colonialism, certain political worldviews in treaty making become a starting point for processes of reconciliation and the fulfillment of treaty obligations between settler Canadians and Indigenous peoples. Underlying this proposition are principles of mutual recognition and sharing of the land and resources. In this article, I borrow James Tully’s concept of small’t’ treaty relations to demonstrate how informal relations between L’sitkuk, clam and other fish harvesters around the world have the potential for regenerating these principles of mutuality as opposed to current formal treaty negotiations that are subjected to what I argue and refer to as political/knowledge ethos.